Assistance for Leading MSME Products of JATAM MPM PDM Sukoharjo Regency in 2025 - Kuswaji Dwi Priyono; Qomarun; Dewi Novita Sari; Basyar Ihsan Arijuddin (Journal of Community Services and Engagement: Voice of Community (VOC), 2026)
This community service program was implemented to strengthen the village agribusiness system through environmentally friendly cultivation, institutional strengthening, product downstreaming, and business legalization facilitation. A before–after (baseline–endline) evaluation approach was applied to measure impacts on production, economic performance, institutional capacity, and market access. Prior to assistance, partners faced moderate productivity, high dependence on chemical inputs, weak collective marketing, limited product differentiation, and inadequate financial administration. After phased mentoring, significant improvements were observed. Farmers adopted organic fertilizers and integrated pest management, reducing chemical input costs and increasing productivity from 5.2 to 5.8 tons/ha. Rice was repackaged into 5 kg and 10 kg branded products, increasing selling prices by 35% and farmer profit margins by 62.5%. Horticulture and livestock products were sorted, hygienically packaged, and labeled, expanding market access and increasing margins by 10–25%. Institutional performance improved through regular meetings, structured financial recording, and collective marketing. Overall, the program transformed subsistence practices into a sustainable, market-oriented collective agribusiness model, enhancing economic resilience and social participation within the farming community.